Estimation of transition process iteration in testing of gas turbine engines - Дмитриев, С. А.; Карпов, А. Е.; Ратынский, В. В.; Шаабдиев, С. Ш. (Proceedings of National Aviation University (archive), 1999)
Considered are questions of increasing efficiency of diagnosing of gas turbine engines for transition modes. Presented are results of research of repeatability transition processed under experimental investigations on gas dynamic stands